Guimarães, Clarice e antes - Bueno, Luís (Teresa, 2001)
Guimarães Rosa and Clarice Lispector have been seen as isolated phenomena in the Brazilian literary history, as if they were responsible for unprecedented pathways in our literature. This work aims to show that this way of seeing it is due less to their works themselves than to the widespread narrow view on the generation that preceded them. In fact, a careful analysis of romances in the 30s shows that in the 40s the Brazilian literary system was already ready for the arrival of Rosa and Lispector.